2016
DOI: 10.1007/s10461-016-1542-3
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and HIV Risk Among Russian Women of Childbearing Age

Abstract: Russia has one of the fastest rising rates of HIV among women in the world. This study sought to identify key factors in HIV transmission among women in Russia. Data were collected as part of a larger clinical trial to prevent alcohol-exposed pregnancies (AEP). Women at risk for an AEP were recruited at women’s clinics; 708 women, aged 18 – 44 (M= 29.04 years), completed HIV risk surveys. Structural Equations Modeling (SEM) was used to test the relationships between alcohol use and sex behavior constructs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…This finding is similar to findings of a systematic review of 20 studies in Africa, 7 which indicated that alcohol drinkers are prone to HIV infection than nondrinkers. Another study by Morris 27 in Kenya, Zambia, and Rwanda, as well as the study by Balachova et al 28 from Russia demonstrated similar findings that revealed a strong association of alcohol use and HIV infection. All these studies pointed out the need for proven behavioral change strategies to be in place, in order to maintain the declining trend of new infection among the youngest age groups.…”
Section: Discussionmentioning
confidence: 52%
“…This finding is similar to findings of a systematic review of 20 studies in Africa, 7 which indicated that alcohol drinkers are prone to HIV infection than nondrinkers. Another study by Morris 27 in Kenya, Zambia, and Rwanda, as well as the study by Balachova et al 28 from Russia demonstrated similar findings that revealed a strong association of alcohol use and HIV infection. All these studies pointed out the need for proven behavioral change strategies to be in place, in order to maintain the declining trend of new infection among the youngest age groups.…”
Section: Discussionmentioning
confidence: 52%
“…In addition to personal and contextual characteristics, lifestyle plays a significant role in the development of risky sexual behaviors. Previous studies have established a significant association between alcohol consumption and higher risks of transmission of HIV and other STDs [ 17 , 18 , 19 ], especially in women [ 4 , 20 ]. Similar results have been found in specific populations, such as MSM, who reduce the use of condoms during anal penetration when they are under the influence of alcohol [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite that, smoking rates and alcohol drinking prevalence during pregnancy have not changed substantially over the last 2 decades 3,10 . Recent prevalence values are 8.5%-14.5% of smokers during gestation [10][11][12] whereas 11%-20% of women drink alcoholic beverages while pregnant 3,[13][14][15] . Both drugs disrupt the development of the nervous system, producing long-lasting neurological and behavioral outcomes in the offspring [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%